Lifestyle as a Mediator of Store Atmosphere, Work Facilities, and Café Visiting Decisions Among Urban Consumers: JEL Classification: M31; D12; D91; L83; Z13 - Yuswari Nur (Journal La Bisecoman, 2026)
This study examines the role of store atmosphere and work facilities in shaping café consumers' visiting decisions, with lifestyle as a mediating variable. A quantitative approach was adopted using structured survey questionnaires administered to 105 respondents in Makassar, South Sulawesi, Indonesia, who regularly use cafés for working, studying, or social interaction. Respondents were selected through purposive sampling, and the minimum sample size was determined based on the number of research indicators. Data were analysed using Structural Equation Modelling Partial Least Squares (SEM-PLS) with SmartPLS 4. The results show that store atmosphere has a positive and significant effect on both visiting decisions and lifestyle, while work facilities significantly influence lifestyle but do not directly affect visiting decisions. Lifestyle positively and significantly affects visiting decisions and mediates the relationships between store atmosphere, work facilities, and visiting decisions. These findings suggest that modern café consumer behaviour is shaped not only by functional aspects of café environments, but also by lifestyle formation, social experiences, and productive activities associated with the work-from-café phenomenon in urban communities.